SHARED SPACE AND CULTURE OF TOLERANCE IN KAMPUNG SETTLEMENTS IN JAKARTA - Freta Oktarina (Fakultas Seni Rupa dan Desain ITB, 2018)
Togetherness and tolerance are among Indonesian traditional cultures which are rarely found in urban society today. The research conducted tried to explore the life of kampung settlements in the center of Jakarta in the era of the 1960s - 1990s, and how the population with a rural background built value of togetherness in the middle of a fast growing city which constantly changes. The study is a historical search to observe the metamorphosis of space and the impact on the pattern of society. The research methodology is carried out through archival and literature studies, followed by field observations and interviews with related actors. The study revealed that in the midst of limited space, the alley as a public space in the kampung, no longer acts just as roads and boundaries between houses, but has shifted into the extention of the house and a shared space for people. The boundaries of private and public areas are blurred in the alley and residents apply the rules of tolerance in using space. After all the alley becomes a binding space between residents Kebersamaan dan toleransi adalah budaya tradisional Indonesia yang sudah jarang ditemukan pada masyarakat perkotaan saat ini. Penelitian ini mencoba melacak kehidupan permukiman kampung di pusat Jakarta pada era 1960- 1990-an dan menelusuri bagaimana penduduk dengan latar belakang pedesaan membangun nilai kebersamaan di tengah kota yang tumbuh dengan cepat dan terus berubah. Penelitian ini merupakan telaah sejarah untuk mengamati metamorfosa ruang dan dampaknya pada pola kehidupan sosial masyarakat. Metodologi penelitian dilakukan melalui studi arsip dan literatur yang dilengkapi dengan observasi lapangan serta wawancara dengan para aktor terkait. Penelitian mengungkapkan bahwa di tengah ruang yang terbatas, ruas gang sebagai area publik di permukiman tidak hanya berfungsi sebagai ruas jalan maupun pembatas antarrumah, melainkan telah menjadi area perluasan rumahrumah penduduk dan ruang berbagi antarwarga. Batas-batas antara area privat dan publik telah menjadi kabur, aturan penggunaan gang ditetapkan berdasarkan azas toleransi. Pada akhirnya gang menciptakan ikatan-ikatan antarwarga dan membangun kebersamaan penduduk.